(3GdJhLjg TQM GdeZfj eNJUQ GdJfHjgs - (3HQgGf GdOjf EHQGgje Hf ehSi GdEjfGSs; (3gHI Gddg Hf YHO GdQMje Hf EHQGgje CHh GdbGSe, TQa GdOjf GHf GdHGQRj GdLgfqj GdMehj,J (B738 (3g` s
(3ChdgG (B:s
(3cJGH GdHjhY s
(3BNQgG (B:s
(3aeG HdZ UMJ efg GdeSdg hgcPG JVY aj GdEfcSGQ Ydi KdGKI hCQHYg hGddg CYde fLR GdLRA GdKGfj ef cJGH GdJhLjI TQM GdeZfj eNJUQ GdJfHjg s
(3GdeZfi eNJUQ GdJfHjg GfXQ cTa GdXfhf L (B1 (3U` (B492s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYj (B443) s
Keywords: (3Gdabg GdTGaYjs